Pemenuhan Hak Pilih Bagi Disabilitas dalam Pemilu oleh KPU di Sumatera Barat - Nurbeti; Helmi Chandra SY (Fakultas Hukum, Universitas Warmadewa, 2021)
Persons with disabilities have the same rights, positions and obligations as other citizens. Based on data on potential electoral voters (DP4) in December 2018, there are 9,172 people with disabilities in West Sumatra. The large number of disailments can provide an opportunity for fraud in general elections. The purpose of this study is to determine the fulfillment of suffrage rights for disabilities, especially in West Sumatra province. The approach in this research is sociological juridical, namely a study that reviews law as a social fact. The results showed that the fulfillment of voting rights for persons with disabilities in simultaneous elections by the General Election Commission (KPU) in West Sumatra was carried out by collecting data, socializing and providing access. Obstacles in fulfilling the right to vote are the family paradigm, the paradigm of officers and the lack of data on disabilities.